THE USE OF PROBLEM BASED LEARNING ON STUDENTS’ WRITING SKILL - Nafisah, Bq. Zuhrotun; Setianingsih, Tri; Qomariya, Siti Syafi’atul (Lembaga Penelitian dan Pendidikan Mandala, 2022)
Abstract (10 Pt)This research aim was to measure the effect of Problem Based Learning towards students’ writing skill. The research was experimental research and the design used was one-group pretest-posttest design. The population of the study was twelve grade students of SMAN 1 Gunungsari. The class were selected as the samples was XIIA social class as experimental group consisted of 15 students from even serial number and XIIB Social class as control group consisted of 15 with odd serial numbers. The Experimental group was treated by Problem based Learning and control group was given treatment without Problem based Learning method. The instrument used in this research was writing test. In analyzing the data, the researchers used statistical analysis by SPSS software, in which it showed that the sig value of = 0.000 was lower than 0.05. Therefore, according to the results of the analysis, it could be concluded that there was a significant difference in students‟ of writing skill by using Problem based Learning method and those who taught without the Problem Based Learning method at SMAN 1 Gunungsari.